Effect of extracellular polymeric substances (EPS) conditioned by combined lysozyme and cationic polyacrylamide on the dewatering performance of activated sludge. (November 2019) - Lin, Feng; Zhu, Xiaolin; Li, Jigeng; Yu, Peiran; Luo, Yong; Liu, Mengru
Abstract: Extracellular polymeric substance (EPS) and the water within it account for about 80% of the total sludge mass, significantly correlated with sludge charge properties, particle size, and dewaterability, while their relation is still ambiguous. To clarify the effect of EPS characteristics on the activated sludge dewaterability, the sludge conditioned by cationic polyacrylamide (CPAM) and lysozyme alone or in combination was comparatively investigated by the means of the SPSS17 software incorporation with chemical analysis. According to the results, the combined conditioning increased both dewatering extent and dewatering rate with the water content as low as 57.79%. It was mainly attributed to the destruction of microbial cell wall and EPS structure by enzymatic conditioning, beneficial for the release of protein (PN) and polysaccharide (PS), as well as the conversion of intracellular water and some bound water into free water. Additionally, Pearson's correlation and factor analysis confirmed the significant influence of EPS properties on sludge dewaterability and explored their detailed relationship. It was indicated the most crucial factors consisted of PNS (PN in S-EPS), PNL (PN in LB-EPS), PNT (PN in TB-EPS), and PST (PS in TB-EPS) accounted for 72.83% in all of the total variance for the contribution to the dewatered water content. Moreover, the high concentration of PNS and PNL led to the zeta potential rising to −9.74 mV, and the destruction of EPS structure was favorable for sludge to form smaller particle size and compact floc structure. All the results were confirmed by the microstructure changes of the sludge flocs. Graphical abstract: Image 1 Highlights: LZM-CPAM conditioning improved the dewatering rate and extent of activated sludge. Factor analysis provided a new insight into the role of EPS in sludge dewatering. PNS, PNL, PNT, and PST were of significant importance to the sludge dewaterability.